Breakdown of water super-permeation in electrically insulating graphene oxide films: role of dual interlayer spacing. (7th June 2018) - Kavitha, Maheshwari Kavirajan; Sakorikar, Tushar; Vayalamkuzhi, Pramitha; Jaiswal, Manu
Abstract: Conventional graphene oxide (GO) is characterized by low sp 2 content in a sp 3 rich matrix, which is responsible both for electrical insulation and water super-permeation. Upon reduction, electrical conduction is achieved at the expense of water permeation ability. Here, we demonstrate that charge conduction and water permeation can be simultaneously restricted in a functionalized form of GO. Gravimetric studies reveal that diffusion of water vapor through a glassy polymer membrane is arrested by loading a hydrophobic form of GO (H-GO) in the polymer matrix, even as such, water inhibition cannot be realized by substantially increasing the thickness of the bare polymer. As an application, the ability of the coating to impede the degradation of methyl ammonium lead iodide films under high humidity conditions is demonstrated. At the same time the H-GO film has a resistance over 10 7 times higher when compared to thermally reduced GO of similar sp 2 fraction. We attribute this unique behavior to the presence of a sub-micron matrix of GO with simultaneous presence of large (∼9.5 Å) and small (∼4.7 Å) interlayer spacing. This leads to disruption of the spatially distributed percolation pathways for electrical charge, and it also serves to block the nanocapillary networks for water molecules.